Integrated management system audit and effectiveness of the mining sector in Perú - Zegarra Talavera, René (2022)
Objective: Determine the audit of the Integrated Management System and its effective improvement of the mining sector in Peru, specifically, in terms of quality, environmental, safety and occupational health management. Method: This research was developed under a quantitative approach, with a non-experimental, correlational and cross-sectional design, which contemplated the application of surveys to 42 managers of a sample of 21 mining projects registered in the Ministry of Energy and Mines (MINEM). Results: The ISO 14001 Standards are positively related to the effectiveness of the mining sector, specifically in environmental management (R: 0.487, Sig.: 0.001); OSHAS 18001 Standards have a positive relationship with the efficiency of the sector both with occupational health and safety management (R: 0.533; Sig.: 0.000); ISO 9001 Standards show a positive relationship with the effectiveness of the sector in quality management (R: 0.382; Sig.: 0.012). Conclusion: The audits of the integrated management systems effectively improved the mining sector, which generates a positive influence on companies and communities.